Crescimento de plantas jovens de pau d'alho (Gallesia integrifolia) cultivadas em diferentes níveis de luminosidade e regime hídrico - Firmino, Taysi Pereira (2016)
Responses morphological and physiological of Gallesia integrifolia (Spreng.) Harms. Plants submitted to several levels of luminosity and water regime are evaluated. Gallesia integrifolia, popularly known as pau d´alho in Brazil, belongs to the Phytolaccaceae family and is native in Brazil. It is characterized by a strong smell of garlic in days with high air humidity. Experiments were conducted at the vegetation greenhouse of the Department of Biology of the Universidade Estadual de Maringá, Maringá PR Brazil, between September 2014 and February 2015. Study on the initial growth of seedlings was undertaken at 30 days intervals for each assay, with 30, 60 and 90 days after the start of the water stress treatment, at six different places, with three light levels (full light; with 50% and 80% shade) and two hydric regimes (plants irrigated daily and plants irrigated only twice a week). Results showed that light was the factor with the greatest effect on plant growth. At the start of the evaluations (30 days), the interaction light and water availability influenced the dry matter of the root, total dry matter and all ratios of plant dry matter under 80% shading. At 90 days, the interaction of variation factors influenced the dry matter of the stem, aerial part and the diameter of the root-stem segment, which were lower in plants under 80% of shading. Light and water availability interaction increased the ratio between the leaf area and the specific leaf area of the plants under 80% shading. The mycorrhizal association of young Gallesia integrifolia plants favored their establishment even in plants with water restrictions. Physiological evaluations (photosynthesis, chlorophyll-a fluorescence, quantification of photosynthetic pigments and non-structured carbohydrates) were also performed. The concentration of total soluble carbohydrates in the Gallesia integrifolia leaves did not show any significant difference after 30 days from the start of the water stress period among treatments. The highest starch concentration rate occurred in plant leaves under 50%water, 80%water, 80%stress and SS+water. Highest starch rate in plants under 50%stress, 80%water, 80%stress and SS+water occurred in the stem, whereas in plants under SS+stress the highest starch rate occurred in the stem and in the root. Total chlorophyll rates were highest in leaves of the third node and cotyledons under greater shading. On the 30th day, stomata conductance was lowest in plants under 80%stress and differed from plants under 50%water. Further, on the 90th day, significant differences were not detected for all photosynthesis parameters. On the 30th day, potential quantity efficiency of photosystem II was lowest for plants under a greater light availability, regardless of hydric availability. On the 90th day, there was no difference between treatments. On the 90th day, the anatomical characteristics of leaves and roots at different sites were assessed. Gallesia integrifolia plants provided dorsiventral leaves with uniserial, glabral and hypostomatic epidermis at both surfaces. Total leaf thickness was greater with increased light levels, regardless of stress. Plasticity index proved to be different between the measured plasticity under light without and with stress. Leaves developed under stress had lower values in plasticity rates perhaps due to costs in plasticity maintenance. Under stress conditions, inadequate phenotypes may emerge with badly adapted plasticity. The roots of the Gallesia integrifolia plant did not reveal any significant difference in their anatomical features in all analyzed treatments. Roots have a different growth type from the pattern described above for most species, called anomalous, with changing variants.